The front page as a canvas for multimodal argumentation: Brexit in the Greek press - Serafis, Dimitris; Tseronis, Assimakis (Frontiers in Communication, 2023)
In this paper, we analyze the front pages of mainstream Greek newspapers with the highest circulation reporting the official result of the Brexit referendum in 2016. Our analysis seeks to extract the standpoints and arguments that circulated in the Greek mainstream press on that day by studying the headlines and visuals on the front page. We study the front page not merely as an informative genre but crucially as an argumentative one, where the arguments can be reconstructed with the help of tools from argumentation theory combined with principles from multimodal critical discourse analysis. The proposed approach makes it possible to compare how the different ideological orientations in the Greek public sphere were steered by the representation of this piece of news. We show that, despite their ideological background, the newspapers under study converge to the construction of Brexit as a menacing phenomenon that puts the EU integration to the test and, as such, as an event that should have been avoided.